Pengaruh Komunikasi Interpersonal Customer Service Go-Jek Indonesia Terhadap Loyalitas Pelanggan Di Jabodetabek - Rizky, Sarah Vania; Sharinta, Elvira Joelanda; Jurdjo, Deonita Putri (The Indonesian Journal of Social Studies, 2020)
Interpersonal communication is one important aspect of customer service in a company that engaged in services. This research was conducted to observe the influence of interpersonal communication of Go-Jek Indonesias customer service on customer loyalty in Jabodetabek and what other factors may come into play to achieve such a result. The principle theory used in this research is the theory of interpersonal communication with customer loyalty as the supporting theory. The research method used is the quantitative explanative method, by distributing questionnaires to 100 respondents of Go-Jek Indonesias users who have contacted the customer service. This research uses the Likert scale as the measurement scale. The results of the research found the contribution of interpersonal communication of Go-Jek Indonesias customer service value equals to 37,3% on customer loyalty in Jabodetabek, with a result of regression coefficient value equal to 0,552 and constant value equal to 32,444.